Test of global monopole based alternative dark matter model from gravitational lensing studies. (3rd June 2021) - Sarkar, Kabita; Ghosh, Samrat; Bhadra, Arunava; Mukhopadhyay, Amitabha
Abstract: Non-minimally coupled global monopole or a Schwarzschild black hole that swallowed a global monopole at the center of a galaxy can correctly describe the observed flat rotation curve of galaxies without the need of dark matter. To become a viable alternative to dark matter the global monopole based model also needs to explain the other observations hinting for the existence of dark matter. Here we have studied weak gravitational lensing due to Schwarzchild space time with global monopole and compare with the findings of galaxy-galaxy weak lensing and also the lensing observations of the rich galaxy cluster Abell 370. We find that global monopole based model cannot describe the mentioned lensing observations without the presence of dark matter.